Penerapan Metode Praktikum Berbantuan Diagram Vee Untuk Meningkatkan Literasi Sains dan Sikap Sains Siswa Pada Materi Ekosistem Kelas VII SMPIT Bina Ummah - Asih, Senjha Mutiara; Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2023)
This study aims to determine the increase in scientific literacy and scientific attitude of students through practicum learning with vee diagrams on ecosystem material. The method used in this research is a quasi-experimental with